Abdominal wall movement in normals and patients with hemidiaphragmatic and bilateral diaphragmatic palsy. Issue 5 (October 1977) - Higenbottam, TIM; Allen, Dave; Loh, L.; Clark, T. J. H.
Abstract : Higenbottam, T., Allen, D., Loh, L., and Clark, T. J. H. (1977). Thorax, 32, 589-595. Abdominal wall movement in normals and patients with hemidiaphragmatic and bilateral diaphragmatic palsy. The abdomen and ribcage volume contribution to the tidal volume have been determined using magnetometers in three groups of subjects—normal males, patients with hemidiaphragmatic palsy, and patients with bilateral diaphragmatic palsy. In all three groups the main moving parts appear to be the anterior surfaces of the abdomen and ribcage even in the presence of bilateral diaphragmatic palsy. In the group of patients with bilateral diaphragmatic paralysis the anterior abdominal wall moved inward paradoxically on inspiration. This `negative' movement increased with larger tidal breaths and was best seen in recumbent patients. The normal subjects and those with hemidiaphragmatic palsy showed an outward movement of the anterior abdominal wall on inspiration which increased with larger tidal breaths. It is believed that the paradoxical movement of the abdomen in bilateral diaphragmatic palsy is a valuable clinical sign of this condition. The contribution of the abdominal volume displacement to the tidal volume in the normal subjects and the hemidiaphragmatic palsy patients varied considerably between subjects and with different postures, but no difference could be discerned between the two groups. This supports the suggestion that the diaphragm is concerned more with maintaining a pressure difference between the abdomen and ribcage than displacing abdominal volume.